2017
DOI: 10.1007/978-3-319-59265-7_1
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Injection and Jamming Attacks in Wireless Secret Sharing Systems

Abstract: Secret key generation (SKG) schemes have been shown to be vulnerable to denial of service (DoS) attacks in the form of jamming and to man in the middle attacks implemented as injection attacks. In this paper, a comprehensive study on the impact of correlated and uncorrelated jamming and injection attacks in wireless SKG systems is presented. First, two optimal signalling schemes for the legitimate users are proposed and the impact of injection attacks as well as counter-measures are investigated. Finally, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 32 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…This signal is known to be Gaussian [15]; hence, a good choice for X J is to be constant, so that, the overall injected signal is an optimal complex zero-mean circularly symmetric Gaussian signal, W ∼ CN (0, σ 2 J Γ). A countermeasure to injection attacks can be built by randomizing the pilot sequence exchanged between Alice and Bob [8], [14]. Here, we propose to randomize the pilots by drawing them from a (scaled) QPSK modulation, as follows: instead of transmitting the same probing signal X, Alice and Bob transmit independent, random probe signals X and Y , respectively, drawn from i.i.d.…”
Section: Mim In W-skg Systems: Injection Attacksmentioning
confidence: 99%
See 1 more Smart Citation
“…This signal is known to be Gaussian [15]; hence, a good choice for X J is to be constant, so that, the overall injected signal is an optimal complex zero-mean circularly symmetric Gaussian signal, W ∼ CN (0, σ 2 J Γ). A countermeasure to injection attacks can be built by randomizing the pilot sequence exchanged between Alice and Bob [8], [14]. Here, we propose to randomize the pilots by drawing them from a (scaled) QPSK modulation, as follows: instead of transmitting the same probing signal X, Alice and Bob transmit independent, random probe signals X and Y , respectively, drawn from i.i.d.…”
Section: Mim In W-skg Systems: Injection Attacksmentioning
confidence: 99%
“…In recent works it has been shown that building semantically secure AE protocols using the W-SKG procedure is straightforward, as long as the channel probing phase of the scheme is robust against active attacks [4], [8]. Therefore, an important next step is to study MiM and denial of service (DoS) attacks during the channel excitation phase of the W-SKG protocol, commonly referred to as "advantage distillation" [4].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the employment of physical layer security (PLS) approaches is currently being considered for beyond fifth generation (B5G) systems. In this direction, a promising alternative to PKE for key agreement is offered by secret key generation (SKG) from shared randomness [5]. The task of SKG from correlated observations was first studied in [6] and [7].…”
Section: Introductionmentioning
confidence: 99%
“…An explanation of the optimality of this choice under different attack scenarios is discussed in[5].…”
mentioning
confidence: 99%
“…A promising avenue in this direction is offered by physical layer security (PLS) that has gained significant attention in recent years in the information theory and communications communities. Of particular interest in PLS technologies are techniques for secret key generation (SKG) from shared randomness that have been shown to provide a viable alternative for quantum resistant, lightweight, key generation and distribution [4]. The task of SKG from correlated observations was first studied in [5] and [6].…”
Section: Introductionmentioning
confidence: 99%